Transformasi Digital Administrasi Madrasah: Optimalisasi Layanan Berbasis Web dalam Meningkatkan Kepuasan Publik - Amiga Putri Minanda; Anatun Nisa Mun'amah; Nurul Mailani (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2025)
Digital transformation has encouraged Madrasah to reposition their administrative role as providers of administrative services that are responsive to user needs and focused on stakeholder satisfaction. The purpose of this study is to analyze digital transformation strategies in the provision of web-based administrative services at MAN Lima Puluh Kota. The method used was qualitative, using a case study as the research method. Data collection techniques included in-depth interviews, participant observation, and documentation studies. Data analysis utilized the interactive model of Miles and Huberman-Saldana, with the following stages: data collection, data reduction, data presentation, and conclusion drawing. The research results show that 1) The digital transformation strategy at MAN Lima Puluh Kota focuses on migrating manual databases to a web-based administration system. 2) Service optimization is carried out by simplifying bureaucratic flows through self-service features for users to increase service responsiveness. 3) Achieving public satisfaction remains adaptive and is heavily influenced by the intensity of system socialization to users. Research findings reveal a major obstacle to resistance to changes in work culture and the need to strengthen a more stable digital infrastructure.